Legal Analysis of the Implementation of Employment Agreements for Laborers or Workers in the Industrial Sector - Nur, Rahmawati; Hijadz, Muhammad Kamal; Salle, Salle (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to analyze legal reform efforts in Indonesia to protect consumers in the digital era and to prepare consumers to face the era of rapid technological developments in digitalization. The method applied in this study is a normative method with a descriptive approach to identify regulatory gaps and challenges in their implementation. The results of the study show that although Indonesia has several regulations related to consumer protection in the digital world, regulatory reform is still very much needed, especially regarding personal data protection and more effective dispute resolution. In addition, consumer readiness in facing the digital era is also influenced by low digital literacy, which is an obstacle to increasing awareness of consumer rights. The government, digital platforms, and consumer protection institutions need to work together to improve public understanding of their rights and obligations as consumers in the digital era.